Developing of Integrative Ecotourism in Waifoi Village, Papua Barat, Indonesia - Mutiono Mutiono (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
Community empowerment carried out in Waifoi village in the process has dynamics that can be understood as material for developing community empowerment processes and formulating empowerment activities appropriate to the local community's context. The purpose of this study is to uncover the dynamics of community empowerment in Waifoi village and describe the innovative formulation of empowerment activities in accordance with the context of community needs in Waifoi village in a participatory manner. The research method used was a case study and participatory rural appraisal through observation, incidental interviews, focus group discussions and document studies which were analyzed descriptively. The results showed that the Waifoi Village community was a type of community that was open to developing innovation but had a socio-cultural context of hunting and gathering types. There is a differentiation of perception in the community structure of Waifoi village regarding interest in the object to be developed in the village. Empowerment through the formulation of integrated village-based ecotourism development can be an alternative that can be drawn from the results of a participatory community needs tracking done.